A MORPHOLOGICAL ANALYSIS OF DERIVATIONAL AND INFLECTIONAL MORPHEMES - Tri Indah Rezeki; Rakhmat Wahyudin Sagala (STKIP Budidaya Binjai, 2019)
Morphological analysis is the main areas in studying vocabulary. Morphological analysis itself is analysis that is breaking a word into its elements (root, prefix and suffix). This study was conducted to analyze the use of derivational and inflectional morphemes in the song lyric “A thousand years” by Christina Perri. This study applied descriptive qualitative research which researchers found out the derivational and inflectional suffixes from the words in “A thousand years” lyric. The results of analyzing data were found in this study are derivational morphemes –ly consist of 2 words and inflectional morphemes –s plural, -s third singular person present tense, -ed past tense, -ing progressive and –er comparative consist of 57 words.